Effects of heat stress on fattening performance, carcass traits, oxidant/antioxidant status, and hepatic heat shock protein 70 levels in different plumage colors of Japanese quail (Coturnix coturnix japonica) - Aslan, S.; Baykalir, Y.; Simsek, U. G.; Gul, B. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2022)
The aim of this study was to investigate the impact of heat stress on production performance and oxidative stress in different plumage colors of Japanese quail. For this purpose, a total of 100 birds were used in this study. The 25 birds belonged to Wild-type (n=25, grey), Tuxedo (n=25, black), Golden (n=25, yellow) and Recessive white (n=25). The birds were reared for 42 days in an environmentally controlled room at 39 degrees C and relative humidity of 60-65%. The body weight, body weight gain (g/bird/day), and feed conversion ratio were not different between the groups (p>0.05). However, the feed intake (g/bird/day) of the Wild-type had a higher value than the Tuxedo (black) group counterparts between 15 and 21 days different (p<0.05). There was no significant effect of heat stress on the carcass traits (p>0.05). Spleen weights were different between the groups (p<0.05). The yellow group had the highest spleen weight. The highest MDA level was found in the Recessive White variety, followed by Wild-type (grey), Golden (yellow) and Tuxedo (black), respectively. However, there were no statistical differences amongst the groups (p>0.05). There was also no statistical significance in glutathione (GSH) and superoxide dismutase (SOD) levels (p>0.05). The heat shock protein 70 kDa (HSP70) level was significantly different between the groups (p<0.001). The highest percentage was observed in the Golden (5.06%) and the lowest in the White (1.43%) variety. There was no superior color variety of Japanese quail regarding fattening performance and carcass traits. It is conceivable that when considering the stress response of the different colors, the Golden group is more sensitive to stress due to the hepatic and cellular level of HSP70.
Keywords: biochemistry; carcass yield; heat stress; quail